Elite sprinting: are athletes individually step-frequency or step-length reliant? - Salo, A. I.; Bezodis, I. N.; Batterham, A. M.; Kerwin, D. G. (Medicine & Science in Sports & Exercise, 2011)
PURPOSE: The aim of this study was to investigate the step characteristics among the very best 100-m sprinters in the world to understand whether the elite athletes are individually more reliant on step frequency (SF) or step length (SL).